An evaluation of chromogranin A versus gastrin and progastrin in gastrinoma diagnosis and control. (April 2014) - Rehfeld, Jens F; Bardram, Linda; Hilsted, Linda; Goetze, Jens P
Aim: The value of chromogranin A (CgA) versus gastrin and progastrin in diagnosis and control of gastrinoma patients is not settled because the peptides circulate as variable mixtures. We have addressed this complexity using defined sequence-specific assays.Patients & methods: Six assays were applied to plasma from 40 gastrinoma patients to measure α-amidated gastrins, glycine-extended gastrins, the total progastrin product, and assays for CgA sequence (340–348) and the 'total' CgA product.Results: The gastrin/progastrin parameters did not add to the diagnosis beyond that of α-amidated gastrins, except in one patient. All gastrin parameters correlated otherwise closely. The CgA results differed. Thus, 11 patients had normal CgA concentrations. By contrast, all total CgA concentrations were elevated but correlated only moderately to gastrin.Conclusion: Assays measuring α-amidated gastrins have high diagnostic value except for singular patients in whom only progastrin was elevated. By contrast, CgA measurements are not valid in diagnosis or control of gastrinomas.